Proclus and his Legacy - Layne, Danielle; Butorac, David D. (Millennium-Studien / Millennium Studies, 2017)
Proclus and his Legacy bridges a gap in scholarship, specifically the last great head of the Platonic Academy, Proclus, and his influence in the history of philosophy and theology. These essays offer not only a companion to Late Antique metaphysics, epistemology, theology and ethics it also explores his reception in the immediate Christian, Jewish and Muslim traditions within the mediaeval, renaissance and modern eras.